„Religion and Ecology” – The New Scientific Paradigm - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2009)
Ecological Crisis is one of the most valid and actual issues of the 21st century. People became conscious of the danger for the whole life on our planet. Nowadays almost all are engaged in the issue: politicians, scientists, artists, community authorities, journalists, ordinary people and even religious leaders. Since the early 1980s scientists tried to involve religion in the ecological field because of the long-term experience of religions in changing ordinary people’s live style. It seems that without essential change of the live style we will not secure basic resources for the future generations. Significance of the situation recognized also theologians and religion scientists from many religious traditions who started scientific research on ecological crisis from their point of view. Mary Tucker and John Girm organized in Harvard University (1996-1998) series of twelve conferences on ecology and different religious traditions. As the outcome of the conferences they founded Forum on Religion and Ecology which became a great platform for exchanging ideas and starting cooperation for the research on the issue. In the late 1990s in some universities were started first lectures concerning religion and ecology. Now several American and European universities propose graduate, postgraduate and even doctoral programs on religion and ecology. It seems that the new scientific field – „religion and ecology” is shaping in order to help recognize the ecological crisis in a wider perspective.